Studi Kelayakan Penuntun Praktikum Asam Basa Berbasis Bahan Lingkungan Menggunakan Model 3-D Dan Penerapan Metode Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar Siswa SMA Negeri 1 Tenga - gerry lumolos; Dokri Gumolung; Joice Caroles (Chemistry Department, Universitas Negeri Manado, 2019)
Practicum guides are printed teaching materials that students can use in the learning process. This development research aims to determine the feasibility of an acid base-based practicum guide for environmental materials with a 3-D model and to improve student learning outcomes through practicum activities and the application of guided inquiry methods. The subject of this research was class XI IPA 1 at SMA Negeri 1 Tenga. The feasibility test for large groups has an average percentage of 88.24% which means that this practical guide is suitable for use with valid qualifications. Student learning outcomes using post test scores with the technique of statistical analysis of one sample t-test (one sample t-test). The results of the one-sample t-test hypothesis at a level of α = 5% were obtained tcount = 4.604> ttable = 1.708. The results of this study indicate that the guidelines for acid-base-based practicum for environmental materials are appropriate to be used in chemistry learning, and the use of acid-based practicum guides for environmental materials with the application of guided inquiry methods can improve student learning outcomes in acid-base material